Mundum, Mundumlore, and Mundumlogy: Toward a Trend Conspectus - Rai , Tara Mani (Kirat Pragya किरात प्रज्ञा, 2026)
This paper examines scholarship on Mundum, Mundumlore, and Mundumlogy among the Kirati peoples of eastern Nepal. It is based on a qualitative literature review and trend analysis of publications from 1978 to 2025. The study identifies patterns in research focus, methodology, and community representation. It also assesses decolonial perspectives. These perspectives interpret Mundum as an indigenous epistemological system. The findings reveal a clear evolution in documentation. Early work focused on preservation-oriented compilations (1994–2001). More recent publications (2015–2025) are systematic and community-based. Five dominant research areas have emerged: linguistic studies of ritual language, ethnographic studies of ritual specialists (shamans), mythological interpretations, indigenous knowledge and cultural identity, and language endangerment. Early scholarship remained largely descriptive. Recent decolonial approaches, however, frame Mundum as a philosophy encompassing cosmology and ecological knowledge. Significant gaps persist in philosophical analysis, gender dimensions, comparative studies, digital preservation, and interdisciplinary approaches. The study concludes that Mundum constitutes a comprehensive indigenous knowledge system. It further argues that Mundumlogy offers an alternative mode of knowledge production that challenges Eurocentric paradigms and contributes to epistemic justice and cultural sustainability.